Saudi female students' motivations to study in Australia: A qualitative study. Issue 1 (1st March 2019) - Binsahl, Haifa Mohammad; Chang, Shanton; Bosua, Rachelle
Many transient Saudi Arabian students arrive in Australia annually; more than 5000 new Saudi students enrolled in 2017 to join thousands of tertiary students already in Australia. This article specifically explores the motives of Saudi female international students (SFIS) for leaving Kingdom of Saudi Arabia (KSA) to study in Australia. Data were analysed and evaluated in terms of the 'push–pull explanation' of motivation. Salient push elements included the lack of university places and courses for women in KSA, the influence of close relatives (especially male) and Saudi governmental policies. Pull elements included the safety and tolerance of Australia being perceived to be greater than any other western country, Australia's excellent education system and the relative convenience and ease of Australia's admission process. The study is significant as it is the first that aims to understand Saudi females' motivations for studying overseas, especially in Australia.